MONEY AND CREDIT SYSTEM IN UKRAINE: PROBLEMS AND DEVELOPMENT PROSPECTS ON THE BACKGROUND OF THE WAR - TANASIIENKO, Nataliia; ZABOLOTNA, Sofiia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
This article analyzes the modern condition of the monetary and credit system, its structure and ways of functioning, as well as indicates problems that prevent the establishment of a stable modern monetary and credit system in Ukraine and proposes solutions.At the moment, Ukraine faces two urgent dangers: war in the country and the rapid devaluation of the Ukrainian hryvnia. External military aggression and the rapid collapse of hryvnia`s exchange rate with inflationary pressure in the country leave no opportunity to stabilize or develop the monetary system. Some of the biggest problems also include: “dollarization” of the economy, high corruption levels, limited spread of promissory notes and a low level of monetization. The best prospect for Ukraine is the development of a free trade zone with the European Union, which will enable access of domestic products to the world market. Further opportunities in this area include solving the identified problems by introducing measures to dedollarize the economy, increasing the effectiveness of anti-corruption bodies, developing trade on the open market, supporting the activities of the NBU during martial law and ensuring financial stability and monetization of Ukraine.
Keywords: money and credit system; dedollarization; monetization; corruption; war